Effects of grain size on the performance of brake linings with Al2O3 additives - Karaca, Faruk; Can, Ilhan (Walter de Gruyter Gmbh, 2021)
International organizations such as the World Health Organization (WHO) and the International Labor Organization (ILO) have called for an end to the use of asbestos and its derivatives in all sectors, primarily due to the negative effects on human and environmental health. For this reason, manufacturing and use of asbestos linings are also prohibited in most developed countries. For this purpose, there are many studies in the literature on the development and research of nonasbestos linings. In the literature, topics such as material content, production, cost, braking performances and mechanical properties of composite linings are commonly encountered. With the technology in the developing world, the working conditions of vehicle elements are getting more difficult. For this reason, during braking, the amount of energy required to be damped against the unit area in the pad surfaces increases, and since the lining surface areas get smaller, the operating temperatures exceed the limits of the material components. Under these conditions, the design of the lining material content is extremely important, taking into account parameters such as load and operating conditions, in order to slow down or stop the vehicle safely. In this study, the braking performance, mechanical and tribological properties of the samples obtained from a number of production processes such as mixing, pre-shaping and pressing of the materials by altering the particle sizes (50 mu m, 75 mu m and 125 mu m) of the filler and friction materials used together with powdered alumina (Al2O3) were investigated. The most suitable parameters were determined as lining material for the samples obtained.
Keywords: Brake lining; braking performance; wear; friction; Al2O3